Economic feasibility of water soluble fertilizer in drip irrigated tomato (Lycopersicon esculentum) - PAWAR, D D; DINGRE, S K; KALE, K D; SURVE, U S (The Indian Journal of Agricultural Sciences, 2026)
Response of water soluble fertilizer with drip irrigation was  tested to study effects on growth, yield and quality of hybrid tomato (Lycopersicon esculentum Mill.) cv. Vaibhav and compared with conventional method for 3 years (2008 to 2010) at the Research Farm of Mahatma Phule Agricultural University, Rahuri (Maharashtra), India. The experiment was laid out in a randomized block design with seven treatments replicated three times. Application of water soluble fertilizer through drip irrigation at 100, 80 and 60% of recommended dose in fourteen equal splits at 8-days interval saved 20–40% fertilizer as compared to the farmer’s practice where nitrogen was applied in two equal splits (at planting and 1 month thereafter). Similarly, 14.6% increase in yield with 58% water saving in tomato as compared to farmer’s practice was obtained when only drip irrigation is used. The 80% recommended dose of fertilizer through drip showed 40% increase in yield over surface irrigation. The quality of tomato was improved significantly due to fertigation through drip. The study indicated that yield of tomato can be increased sizably by applying only ‘N’ through drip irrigation and P and K as per conventional practice than only drip irrigation. The continuous availability of nutrients in splits throughout the growth period of tomato resulted into superior yield and quality of tomato. The fertigation resulted into maximum net seasonal income, total net income and net extra income over control and maximum water productivity when 100% fertilizers were applied through drip, however it were on par with the economical parameters obtained at 80% fertilizer application.